Co-delivery of drugs and DNA from cationic core–shell nanoparticles self-assembled from a biodegradable copolymer - Wang, Yong; Gao, Shujun; Ye, Wen-Hui; Yoon, Ho Sup; Yang, Yi-Yan (Nature materials, 2006)
Non-viral gene-delivery systems are safer to use and easier to produce than viral vectors, but their comparatively low transfection efficiency has limited their applications 1 . Co-delivery of drugs and DNA has been proposed to enhance gene expression or to achieve the synergistic/combined effect of drug and gene therapies 2 , 3 , 4 , 5 , 6 . Attempts have been made to deliver drugs and DNA simultaneously using liposomes 7 . Here we report cationic core–shell nanoparticles that were self-assembled from a biodegradable amphiphilic copolymer. These nanoparticles offer advantages over liposomes, as they are easier to fabricate, and are more readily subject to modulation of their size and degree of positive charge. More importantly, they achieve high gene-transfection efficiency and the possibility of co-delivering drugs and genes to the same cells. Enhanced gene transfection with the co-delivery of paclitaxel has been demonstrated by in vitro and in vivo studies. In particular, the co-delivery of paclitaxel with an interleukin-12-encoded plasmid using these nanoparticles suppressed cancer growth more efficiently than the delivery of either paclitaxel or the plasmid in a 4T1 mouse breast cancer model. Moreover, the co-delivery of paclitaxel with Bcl-2-targeted small interfering RNA (siRNA) increased cytotoxicity in MDA-MB-231 human breast cancer cells.